Role of a mental health physician in the management of oncology patients: a case vignette and the need for collaboration - Armiya'u, Aishatu Yusha'u; Akande, Yusuf (Frontiers in Health Services, 2024)
There is an interplay between oncology and mental health, resulting in a high prevalence of mental disorders among cancer patients. Out of the several interventions developed to target cancer specifics, collaborative care is indicated due to its efficacy. The perspective delves into the efficacy of collaborative care models, spotlighting a culturally informed strategy designed to harmonize mental and physical health interventions to bolster the overall wellbeing and resilience of individuals battling cancer. Central to our discussion is a compelling case vignette of Raliat, a patient diagnosed with ovarian cancer whose narrative exemplifies the multifaceted challenges cancer patients face, including stigma, psychological distress, and social isolation. Raliat's story illuminates the profound impact of cultural beliefs on patient experiences and the critical importance of a sensitive, holistic approach to care that respects cultural contexts. Through this lens, our analysis reveals that addressing emotional and situational stressors through collaborative care can significantly reduce oxidative stress, potentially decelerating the progression of both cancer and accompanying mental health disorders. We advocate for integrating mental health services into oncological care, drawing on the case vignette to argue for policies that facilitate such merger by employing validated collaborative care models. We conclude with a call for public education to diminish cancer stigma and improve social outcomes, emphasizing the use of a culture-informed PACER (physical, affective, cognitive, environmental, and relationship) strategy in providing comprehensive care for cancer patients and their families.